Reconsidering regeneration in metazoans: an evo-devo approach - Tiozzo, Stefano; Copley, Richard R. (Frontiers in Ecology and Evolution, 2015)
Regeneration of body structures is an ability widely but unevenly distributed amongst the animal kingdom. Understanding regenerative biology in metazoans means understanding the multiplicity of the cellular and molecular mechanisms that lead to the differentiation, morphogenesis and ultimately the development of a particular regenerating unit. In this manuscript we critically assess the evolutionary considerations suggesting that regeneration is an ancestral trait rather than a mechanism independently evolved in different taxa. As a general method to test evolutionary hypothesis on regeneration, we propose mechanistically dissecting the regenerative processes according to its conserved chronological steps: wound healing, mobilization of cell precursors and morphogenesis. We then suggest interpreting regenerative biology from an evo-devo perspective, proposing a possible theoretical framework and experimental approaches without necessarily invoking a common origin or only multiple losses of regenerative capabilities.